Judaism (New York, 2010)
Explore the wisdom of the ages with this insightful book. Often called the religion of reason, Judaism is abundant with beautiful traditions, ancient customs and scholarly Biblical interpretation. "Revered Wisdom: Judaism" is the perfect introduction to the period that in many ways was the most complex and confusing in Israel's history. The centuries following the Fall of Jerusalem to the death of Herod the Great constitute a reflective and retrospective age, whose writings and teachings reveal the soul of the Jewish faith. The first section contains an expertly revised version of Charles Foster Kent's "The Makers and Teachers of Judaism". Dr. Kent offers a historical interpretation of the critical period in which Judaism was born and attained its full development. The second section features selections from Gustav Karpeles' "Jewish Literature and Other Essays" and provides insightful commentary on subjects such as the Talmud, women in Jewish literature and traditional synagogue music.
Keywords: Religion